Association between fathers' parental mindfulness and adolescent behavioral development and academic grades - Carlson, Michelle, author; Coatsworth, Douglas, advisor; Stallones, Lorann, committee member; Lucas-Thompson, Rachel, committee member (Colorado State University. Libraries, 2017)
This study examined the association of fathers' mindful parenting with adolescent problem behaviors and academic grades. Past research shows positive associations between mindful parenting and youth outcomes and supports the efficacy of parental mindfulness training for improving parent-child relationships and decreasing adolescent problem behaviors. Yet, much of this research is conducted with mothers, whereas fathers are less represented in these studies. Parenting research that has been done with fathers has highlighted the significant impact that a father-child relationship can have on a child's development, suggesting that mindful parenting might also be a useful avenue for study with fathers. In a sample of 244 families with participating fathers, this study tested the association between fathers' mindful parenting and adolescent internalizing behavior, externalizing behavior, and grades after controlling for fathers' general parenting and demographic characteristics. Results indicated that mindful parenting in fathers was associated with youth outcomes above and beyond fathers' general parenting and demographics, but only for youth-report of fathers' mindful parenting. These results indicated that when youth reported more mindful parenting by their father, they also had lower levels of externalizing and internalizing behaviors. Mindful parenting did not significantly predict grades. Outcomes of this study indicate a promising area of research regarding fathering and mindful parenting.